2021
DOI: 10.1038/s41598-021-88410-5
|View full text |Cite
|
Sign up to set email alerts
|

Several frailty parameters highly prevalent in middle age (50–65) are independent predictors of adverse events

Abstract: Although frailty can arise in middle age, very few studies have investigated frailty before 65 years. Our objectives were to assess the prevalence of frailty parameters in middle-aged individuals and probe the association with future adverse events. We performed cross-sectional and longitudinal analyses of community-dwelling individuals aged 50 to 65 (n = 411, median age: 59.0) having undergone a multidomain geriatric assessment (2010–2015) in an outpatient clinic in the greater Paris area of France (SUCCEED c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…First, we found that the effect of frailty on time to first ICU transfer depended on the patient’s age. Although study findings, whereby the average FRS score for each FRS definition significantly increased with age and confirms the increased prevalence of frailty in older adults (Chu et al, 2021; Segaux et al, 2021), the current study found the highest prevalence (using FRS-NF-26-LABS) in the 60 to <70 years age group (56.4%) and not the oldest ≥80 years age group (43.5%).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…First, we found that the effect of frailty on time to first ICU transfer depended on the patient’s age. Although study findings, whereby the average FRS score for each FRS definition significantly increased with age and confirms the increased prevalence of frailty in older adults (Chu et al, 2021; Segaux et al, 2021), the current study found the highest prevalence (using FRS-NF-26-LABS) in the 60 to <70 years age group (56.4%) and not the oldest ≥80 years age group (43.5%).…”
Section: Discussionsupporting
confidence: 57%
“…The present study contributes new information on frailty in hospitalized middle-aged adults (Segaux et al, 2021) and adds to the frailty literature that has primarily addressed older adults 65 or 70 years of age and older based on conceptions of frailty as a geriatric syndrome. Our findings and others (Hanlon et al, 2018; Loecker et al, 2021; Segaux et al, 2021) confirm the importance of assessing frailty in middle-aged adults since this group is not typically considered at risk for frailty and may be overlooked in frailty risk stratification. Contemporary aging theories and research recognize heterogeneity in the aging process and the influence of behaviors, comorbidity, the social environment, and social determinants on health status with negative consequences such as frailty (Buta et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Since many frailty parameters are already altered in middle age and predictive of adverse events, restricting frailty assessment to older age groups overlooks the needs of this vulnerable population and opportunities for prevention and risk mitigation. 63 , 64 , 65 Prior research using the FRS showed a weak effect size for age and FRS scores. 8 , 9 …”
Section: Discussionmentioning
confidence: 95%
“…Due to the negative health outcomes associated with frailty, routine screening and studies have been applied and recommended to populations aged over 65 years [ 11 , 12 , 13 , 14 , 15 ], but there is limited data available regarding middle-aged populations (45–65 years old) or those younger than 45 years old [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%